Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Shaping Social Change with Music in Maputo, Mozambique - Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Manhiça, Anésio (IDS, 2021)
In Mozambique, development programmes have traditionally drawn on music as a means to promote social transformation by educating citizens on key social development issues. Shifting the focus from music as a teaching medium to music as a rich source of information can provide vital insights into public opinion and political ideas, and significantly impact the development of citizen engagement projects. Maximum gains for development and civil society agencies can be achieved by mainstreaming gender into mutual learning activities between singers, audiences, and academics.
Keywords: *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento; gender / género

Juventude urbana e redes sociais em Moçambique: a participação política dos conectados desamparados - Tsandzana, Dércio (Comunicação e Sociedade, 2018)
Nos últimos 10 anos, os estudos sobre a participação política por intermédio das redes sociais marcam o debate na área dos estudos dos média. Em Moçambique, de forma particular, e no mundo, de forma geral, a juventude representa o centro galvanizador que encontra no uso das redes socias uma ferramenta quase ideal de expressão sobre as suas frustrações decorrentes da sua situação de gritante miséria social – desemprego e incerteza de vida constante a que os jovens se encontram expostos. Com o presente artigo, pretendemos analisar o papel das redes sociais, concretamente o Facebook, no engajamento político e social da juventude urbana em Moçambique, considerando um horizonte que abarca os últimos quatro anos, 2014-2017. Como resultado, concluímos que embora a sua expansão nos últimos anos, as redes sociais ainda não podem ser consideradas, no seu todo, como espaços que permitam uma efectiva participação política da juventude, decorrente do facto de a internet ser menos abrangente, por um lado, e do fraco interesse da juventude em questões políticas em Moçambique, por outro. EN: In the last 10 years, studies on political participation through social networks have marked the debate in the field of media studies. In Mozambique, particularly, and in the world, in general, youth represent the galvanizing centre that finds in the use of social networks an almost ideal tool of expression about their frustrations due to their situation of blatant social misery – unemployment and constant life uncertainty to which youth are exposed. With this article, we intend to analyse the role of social networks, specifically Facebook, in the political and social engagement of urban youth in Mozambique, considering a timeline that covers the last four years, 2014 to 2017. As a result, it is concluded that, despite the expansion of social networks in recent years, they cannot yet be considered as spaces for effective political participation by youth, due to the fact that the internet is less comprehensive, on the one hand, and the weak youth interest in political issues in Mozambique, on the other.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; G - south / sul; GD - Beira; GP - Maputo; GP - Sofala; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

'Não fica bem que uma mulher seja chefe quando existem homens'. Género e Pobreza no Sul de Mocambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2010)
Este relatório final é o terceiro da série "Políticas de Género e Feminização da...
Keywords: G - Mozambique / Moçambique; G - south / sul; L - portuguese / português

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização